2009
DOI: 10.1097/ccm.0b013e3181b39f1b
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical practice guideline: Red blood cell transfusion in adult trauma and critical care*

Abstract: Evidence-based recommendations regarding the use of RBC transfusion in adult trauma and critical care will provide important information to critical care practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
222
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 442 publications
(234 citation statements)
references
References 235 publications
5
222
0
4
Order By: Relevance
“…Such uncertainty with respect to an expensive pharmacological intervention would be unthinkable. The results of RCTs in non-cardiac surgery patients may not be transferrable to a population with symptomatic cardiac disease and it is of concern that these, as well as the results of observational studies, which we have concluded are unable to guide transfusion practice, form the basis of national and international blood conservation guidelines 4,5,84 . Such guidelines urge clinicians to adopt restrictive transfusion practices due to the adverse outcomes demonstrated in these studies 4,5 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Such uncertainty with respect to an expensive pharmacological intervention would be unthinkable. The results of RCTs in non-cardiac surgery patients may not be transferrable to a population with symptomatic cardiac disease and it is of concern that these, as well as the results of observational studies, which we have concluded are unable to guide transfusion practice, form the basis of national and international blood conservation guidelines 4,5,84 . Such guidelines urge clinicians to adopt restrictive transfusion practices due to the adverse outcomes demonstrated in these studies 4,5 .…”
Section: Discussionmentioning
confidence: 98%
“…The results of RCTs in non-cardiac surgery patients may not be transferrable to a population with symptomatic cardiac disease and it is of concern that these, as well as the results of observational studies, which we have concluded are unable to guide transfusion practice, form the basis of national and international blood conservation guidelines 4,5,84 . Such guidelines urge clinicians to adopt restrictive transfusion practices due to the adverse outcomes demonstrated in these studies 4,5 . Reduction of this uncertainty requires adequately powered and well conducted RCTs that anticipate the limitations that we have described: they should include patients at high-risk of transfusion (for example by using validated transfusion risk scores), and document measures taken to ensure that other aspects of care are the same across intervention groups, for example by blinding surgeons and anaesthetists to treatment allocation and allowing other staff to make transfusion decisions according to the study protocol.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations